Prognostic value of chromosomal translocations in small‐bowel diffuse large B‐cell lymphoma. Issue 2 (18th June 2015) - Ikegami, Koji; Nakamura, Shotaro; Esaki, Motohiro; Yanai, Shunichi; Hirahashi, Minako; Oda, Yoshinao; Takeshita, Morishige; Matsumoto, Takayuki; Kitazono, Takanari
Abstract : Aims: The objective of this study was to investigate the incidence and clinical significance of lymphoma‐associated chromosomal translocations, particularly those involving the immunoglobulin heavy chain gene ( IGH ) locus, in patients with small‐bowel diffuse large B‐cell lymphoma (DLBCL). Methods and results: Translocations involving IGH,   bcl‐6, MYC and bcl‐2 were investigated with interphase fluorescence in‐situ hybridization on paraffin‐embedded tissues in 35 patients with primary small‐bowel DLBCL, and the overall survival (OS) and progression‐free survival (PFS) rates were evaluated with the Kaplan–Meier method. Translocations involving IGH, bcl‐6, MYC and bcl‐2 were detected in 23 (70%), 12 (36%), eight (24%) and six (18%) of 33 cases, respectively. The patients with IGH translocations showed less frequent relapse or progression of lymphoma (17%) than those without (60%, P  = 0.034). Univariate analyses demonstrated that young age, a low international prognostic index, translocations involving IGH, extra copies of MALT1 / bcl‐2 and bcl‐6 immunoexpression were significantly associated with better OS and PFS. Cox multivariate analysis revealed translocations involving IGH to constitute an independent prognostic factor for better PFS, but not better OS. Conclusions: Translocations involving IGH are frequent in cases of small‐bowel DLBCL. These translocations may be predictive of a favourable clinical course.